Pengaruh Ekstrakurikuler Muhadhoroh terhadap Karakter Percaya Diri Peserta Didik dalam Pembelajaran Tematik - Allinda Hamidah; Intan Sari (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
The 2013 curriculum applies integrated thematic learning with a scientific approach in elementary schools. One of the scientific skills that must be mastered by students in the scientific approach is communicating. The majority of students still find it difficult to form confident characters to master these skills. Related to this, several schools hold extracurricular activities to help students develop their interests, including helping students to build self-confidence. Extracurricular that can form a confident character is extracurricular muhadhoroh. One of the institutions that implement Muhadhoroh Extracurricular is MI Islamiyah Ngarum Lamongan, This study aims to determine the application of extracurricular muhadhoroh, Knowing the confident character, and Knowing the confident character of grade III, IV and V students in thematic learning through MI Islamiyah Ngarum in the academic year 2020/2021, The results of this study indicate that extracurricular muhadhoroh MI Islamiyah Ngarum is included in the active criteria with a percentage value of 69-78%, the character of the students' confidence In class III, IV and V thematic learning at MI Islamiyah Ngarum, it is included in the confidence criteria with the results of the percentage value of 72-90, the value of r calculated based on the results of research data analysis calculated using the product moment correlation formula, namely When compared with r table, the results obtained r count> r table with a significant level of 5% (>0.5140). This shows that the correlation to the influence of Muhadhoroh extracurricular activities on the self-confident character of students in thematic learning for grades III, IV and V at MI Islamiyah Ngarum Medium.